1999
DOI: 10.1046/j.1365-2257.1999.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime treatment costs of β-thalassaemia major

Abstract: Beta-thalassaemia major is a serious genetic disorder, which results in a considerable increase in both acute and chronic morbidity, and mortality. Although beta-thalassaemia major is a rare disease affecting approximately 600 people in the UK, treatment is intensive and predictions of the costs incurred may aid health care planning. In this report, the cost to the health service of providing treatment services for beta-thalassaemia major patients, over the course of a lifetime, is calculated in order to assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…Among the four published studies we identified, [21][22][23][24] only one 22 reported the mean annual ICT per-patient cost, which was estimated to range from $12,719 to $24,845 (USD 1998), but only the costs associated with DFO and home healthcare services were included. In another of these studies, 24 the lifetime cost of DFO was estimated to be about $63,000 (USD 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four published studies we identified, [21][22][23][24] only one 22 reported the mean annual ICT per-patient cost, which was estimated to range from $12,719 to $24,845 (USD 1998), but only the costs associated with DFO and home healthcare services were included. In another of these studies, 24 the lifetime cost of DFO was estimated to be about $63,000 (USD 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only four studies were identified that contained data related to the costs of infused ICT. [21][22][23][24] On the basis of the literature, a single composite list of cost variables (such as drug, equipment, monitoring toxic effects, and psychotherapist) was created to serve as the basis for the health economics component of the case report form. Frequency of use and unit cost data for each of these variables were identified from the literature, this study, administrative databases, and medical supply catalogues.…”
Section: Annual Costs Of Ictmentioning
confidence: 99%
“…One study estimated the undiscounted lifetime cost of treating the disease at £803,002 ($1,332,980). 19 The experience in the UAE demonstrates the value of engaging college students to promote genetic screening. Being educated in the scienc-es, the student ambassadors were quick to grasp the potential value of screening and effective at delivering the message to other students.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…In the developing world, the vast majority of affected children die before the age of 20 years because of the unavailability of most forms of effective treatment. 2,3 The lifetime cost of treating a patient with thalassemia major is estimated to be d80 000 (4US$ 110 000) in the United Kingdom 4,5 and US$ 284 154 in Israel. 6 Recent data from the Taiwan Thalassemia Association indicate that more than 400 patients have b-thalassemia major or other transfusion-dependent thalassemias in Taiwan, and their treatment costs account for a considerable percentage of the Taiwan's National Health Insurance expenditure.…”
Section: Introductionmentioning
confidence: 99%